2016
DOI: 10.1074/jbc.m115.679993
|View full text |Cite
|
Sign up to set email alerts
|

Validation and Characterization of a Novel Peptide That Binds Monomeric and Aggregated β-Amyloid and Inhibits the Formation of Neurotoxic Oligomers

Abstract: Although the formation of ␤-amyloid (A␤) deposits in the brain is a hallmark of Alzheimer disease (AD), the soluble oligomers rather than the mature amyloid fibrils most likely contribute to A␤ toxicity and neurodegeneration. Thus, the discovery of agents targeting soluble A␤ oligomers is highly desirable for early diagnosis prior to the manifestation of a clinical AD phenotype and also more effective therapies. We have previously reported that a novel 15-amino acid peptide (15-mer), isolated via phage display… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 64 publications
0
13
0
Order By: Relevance
“…Gibson and Murphy (2005) previously reported that polyarginine-5 (R5) and KLVFF-R5 peptides broadly increased the aggregation of amyloid-beta 1-42 overall, resulting in the formation of larger amyloid-beta 1-42 aggregates with lower cytotoxicity. Barr et al (2016) reported that a 15-residue cationic peptide, with 20% of its sequence comprised of arginine residues, reduced the formation of soluble, cytotoxic amyloid-beta 1-42 oligomers by driving the aggregation pathway toward the formation of larger, amorphous aggregates; these amorphous aggregates were also observed to have lower cytotoxicity than the oligomers formed by amyloid-beta 1-42 alone. A potential therapeutic mechanism for peptides targeting amyloid-beta could therefore involve the reduction of cytotoxic, soluble oligomeric amyloid-beta species by driving the aggregation pathway toward the formation of non-toxic insoluble aggregate species, rather than aiming to inhibit aggregation.…”
Section: Modulation Of Cytotoxicity Through Effects On Amyloid Formationmentioning
confidence: 99%
“…Gibson and Murphy (2005) previously reported that polyarginine-5 (R5) and KLVFF-R5 peptides broadly increased the aggregation of amyloid-beta 1-42 overall, resulting in the formation of larger amyloid-beta 1-42 aggregates with lower cytotoxicity. Barr et al (2016) reported that a 15-residue cationic peptide, with 20% of its sequence comprised of arginine residues, reduced the formation of soluble, cytotoxic amyloid-beta 1-42 oligomers by driving the aggregation pathway toward the formation of larger, amorphous aggregates; these amorphous aggregates were also observed to have lower cytotoxicity than the oligomers formed by amyloid-beta 1-42 alone. A potential therapeutic mechanism for peptides targeting amyloid-beta could therefore involve the reduction of cytotoxic, soluble oligomeric amyloid-beta species by driving the aggregation pathway toward the formation of non-toxic insoluble aggregate species, rather than aiming to inhibit aggregation.…”
Section: Modulation Of Cytotoxicity Through Effects On Amyloid Formationmentioning
confidence: 99%
“…Equilibrium binding studies yield K D values of 69 and 535 μM for Aβ 42 monomers and oligomers, respectively. In a similar study, Barr et al verified the inhibition of Aβ fibril formation by a 15-amino acid peptide [ 41 ]. SPR surfaces functionalized with monomeric, oligomeric, and fibrillar Aβ 42 revealed a stronger affinity of the polypeptide toward the fibrillar form, although only a K D value of 11 μM was measured by injecting Aβ 42 onto immobilized peptides and no affinity constant was given.…”
Section: Discussionmentioning
confidence: 95%
“…As discussed earlier, CTFs likely coassemble with Aβ42 and form hetero-oligomers that are not toxic. Other inhibitors, including various peptides and small molecules, have been reported to use similar mechanisms for inhibition of Aβ toxicity, that is, binding to and co-oligomerizing with Aβ42 to form nontoxic structures. , Due to the complexity of the relationship between assembly and toxicity inhibition, using assembly inhibition as a strategy for drug design should be considered with caution. Though peptide-based Aβ aggregation inhibitors have been studied for about 20 years now, several key unsolved questions can hinder the drug discovery processes: (1) Why are Aβ oligomers toxic?…”
Section: Discussionmentioning
confidence: 99%